Elementos simétricos sob involuções orientadas em anéis de grupos - Rafael Bezerra dos Santos (2012)
Let R be a commutative ring with identity, G be a group and RG be thegroup ring of G over R. Given an orientation of G and ' an involution inG, consider an oriented involution in RG. The main goal of this work is to obtain necessary and suffcient conditions on the ring R and the group G for (RG), the set of symmetric elements of RG under the oriented involution , to be commutative.